SUSTAINABILITY EVALUATION OF DEWARUCI UNDERPASS INTERSECTIONS - Lawalata, Greece Maria; Satrio, Hendro; Sailendra, Agus Bari (Jurnal HPJI, 2015)
Abstract Indonesian commitment to sustainable development needs to be supported by real actions. Such as to organize sustainable road construction. The Ministry of Public Works Policy related to the field of road has been in line with the international agreement of sustainable development. However, to make sure that road projects have been implemented in sustainable way, a proper assessment of the sustainability measures is required. Dewa Ruci underpass road project was one of case study of sustainable road system rating. The procedure of the rating system is done by collecting the required documents comparing with the sustainable criteria of Green Road Rating System. Road projects in Indonesia have met the technical standards and some of the environmental requirements that have been issued by the Government. Dewa Ruci underpass projects including projects that have met the technical standards and environmental requirements. From the efforts of sustainable practices that have been performed, Dewa Ruci Underpass project was rated according to the rating system, and it reached the level of four stars. The criteria on the Green Roads still have to be disseminated to be known by those stakeholders, besides the need to disseminate the rating system. Thus road projects in Indonesia can be more sustainable. Implementation of sustainable road rating system in Indonesia needs to be supported by dissemination. Keywords: system rating, road sustainable, principle of sustainable road  Abstrak Komitmen Indonesia untuk pengembangan berkelanjutan diperlukan dukungan dengan aksi aksi yang nyata, seperti organisasi konstruksi jalan berkelanjutan. Kebijakan Kementerian Pekerjaan Umum terkait dengan sector jalan telah selaras dengan perjanjian internasional untuk pengembangan berkelanjutan. Walaupun demikian, untuk meyakini proyek proyek dikerjakan secara berkelanjutan, penilaian yang tepat untuk pengukuran keberlanjutan dibutuhkan. Proyek Underpass Dewa Ruci dipilih untuk kasus studi sistem peringkatan jalan berkelanjutan. Prosedur sistem peringkatan dilakukan dengan pengumpulan dokumen dokumen dan dibandingkan dengan Kriteria Sistem Peringkatan Jalan Hijau. Proyek jalan di Indonesia harus memenuhi standar teknis dan beberapa persyaratan lingkungan yang ditetapkan pemerintah termasuk Underpass Dewa Ruci. Ditinjau dari upaya keberlanjutan yang dihasilkan, Underpass Dewa Ruci telah dinilai sesuai dengan sistem peringkat jalan dan mencapai peringkat bintang empat. Kriteria jalan hijau perlu didesiminasikan kepada seluruh pemangku kepentingan, khususnya sistem peringkatannya. Lebih lanjut, proyek proyek jalan di Indonesia akan dapat lebih berkelanjutan. Implementasi peringkatan jalan berkeselamatan perlu didukung dengan upaya-upaya diseminasi. Kata-kata kunci: sistem peringkatan, jalan berkelanjutan, prinsip prinsip jalan berkelanjutan.